2009
DOI: 10.1001/jama.2009.265
|View full text |Cite
|
Sign up to set email alerts
|

Live Attenuated or Inactivated Influenza Vaccines and Medical Encounters for Respiratory Illnesses Among US Military Personnel

Abstract: ILITARY PERSONNEL ARE prone to outbreaks of respiratory illness such as influenza for a variety of reasons, including crowding and stressful conditions. 1-3 Before the availability of an influenza vaccine, the military population experienced high mortality and morbidity during such outbreaks. Trivalent inactivated vaccine (TIV), administered intramuscularly, was first developed and tested in the military in the 1940s and has been used annually since the 1950s to prevent influenza and its complications. 4 In 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 32 publications
1
63
0
2
Order By: Relevance
“…In a randomized, double-blind, placebocontrolled trial conducted among young adults during the 2004-05 influenza season, when the majority of circulating A(H3N2) viruses were antigenically drifted from that season's vaccine viruses, the efficacy of LAIV3 and IIV3 against cultureconfirmed influenza was 57% (95% CI = -3-82) and 77% (95% CI = 37-92), respectively. The difference in efficacy was not statistically significant and was attributable primarily to a difference in efficacy against influenza B (256) (260). However, in a retrospective cohort study comparing LAIV3 and IIV3 among 701,753 nonrecruit military personnel and 70,325 new recruits, among new recruits, incidence of ILI was lower among those who received LAIV3 than IIV3.…”
Section: Comparisons Of Laiv3/4 and Iiv Efficacy Or Effectivenessmentioning
confidence: 89%
“…In a randomized, double-blind, placebocontrolled trial conducted among young adults during the 2004-05 influenza season, when the majority of circulating A(H3N2) viruses were antigenically drifted from that season's vaccine viruses, the efficacy of LAIV3 and IIV3 against cultureconfirmed influenza was 57% (95% CI = -3-82) and 77% (95% CI = 37-92), respectively. The difference in efficacy was not statistically significant and was attributable primarily to a difference in efficacy against influenza B (256) (260). However, in a retrospective cohort study comparing LAIV3 and IIV3 among 701,753 nonrecruit military personnel and 70,325 new recruits, among new recruits, incidence of ILI was lower among those who received LAIV3 than IIV3.…”
Section: Comparisons Of Laiv3/4 and Iiv Efficacy Or Effectivenessmentioning
confidence: 89%
“…Three randomized, controlled efficacy trials in children of Ͼ6 months and Յ18 years of age consistently demonstrated that LAIV was significantly more protective than IIV (4)(5)(6)(7). Similarly, for adults older than 16 years, some comparative trials showed that LAIV was at least as effective as IIV (8)(9)(10). However, 2 adult trials showed that IIV was more protective than LAIV (11)(12)(13), and thus there is some controversy over whether LAIV can be as effective as a well-matched IIV seasonal vaccine for adults with previously extensive influenza virus exposure (2,14).…”
mentioning
confidence: 97%
“…In contrast, LAIVs induce both humoral and cellular immunity, but are restricted for use in persons aged 2-49 y (6,7). Moreover, recurrent administration of LAIVs, which use the same attenuating viral backbone, could result in tolerance in repeat recipients (8).…”
mentioning
confidence: 99%